Hidrólise de palha e casca de arroz para produção de etanol de segunda geração (2G) - Suyama, Heitor (2019)
This research presented the evaluation of acid hydrolysis of straw and rice husk for the production of 2G ethanol, under different conditions using experimental design. The lignocellulosic raw material used was crop residue formed by the mixture of husk and rice straw, in equal parts and without any previous treatment, ground in a hammer mill. The hydrolysis of the biomass was carried out under heating at temperatures of 30, 50 and 70 ºC, after pre-treatment of hydration, added with phosphoric acid solution, 5, 10 and 15%, exposure to ultrasound at times 5, 10 and 15 minutes, according to experimental design 2 3. The evaluation of the process was performed by the soluble solids content obtained by refractometry in ° Brix. The hydrolysates were fermented using the yeast Sacaromyces cerevisiae SC (CA-11) under rotational agitation, at 36 ºC, 130 rpm, for 48 hours. The ethanol content obtained was evaluated by gas chromatography. The statistical analysis of the results evaluated the influence of the effect of the variables, hydrolysis temperature, time of exposure to ultrasound and acid concentration. The results indicated that the concentration of 15% phosphoric acid followed by the temperature of 70 ºC were significant variables. The analysis of the estimated effects and the response surfaces confirmed that the hydrolysis temperature, the concentration, and the interaction between the temperature and concentration were statistically significant in the hydrolysis of the material used and resulted in a model with good adjustment between the predicted values and the values obtained experimentally. This indicates that it can be used in the prediction of ° BRIX values, within the studied limits. The statistical analysis of the ethanol results indicated that the temperature was statistically significant, while the acid concentration and the time of exposure to ultrasound were not significant under the conditions studied.